ANALISIS TEKNIK PERMAINAN TRUMPET PADA LAGU CARNIVAL OF VENICE OLEH WYNTON MARSALIS (Jurnal Sitakara, 2026)
The aim of this research is to: 1) Describe the analysis of trumpet playing techniques in the song Carnival of Venice by Wynton Marsalis. 2) Describe the interpretation of the song Carnival of Venice by Wynton Marsalis. The theories used in this research are analysis theory, playing techniques, and interpretation. The method employed is a qualitative descriptive method, with the research sample comprising the video and sheet music of Carnival of Venice. Data collection techniques include observation, documentation, and laboratory work. The research results show: 1) The analysis of trumpet playing techniques in Carnival of Venice by Wynton Marsalis focuses on techniques such as Lip Trills, Double Tonguing, Triple Tonguing, and Circular Breathing. 2) The interpretation of Carnival of Venice is observed through various tempos (Allegretto, Andante) and dynamic markings (Piano, Forte, Crescendo, Decrescendo). This piece aims to showcase the performer's ability to deliver the song with both the complexity of trumpet playing and the overall beauty of the music.Kata Kunci : Analisis, Teknik Permainan, Trumpet, Interpretasi.